Learning Achievement from Blended Learning in Information Searching and Academic Writing of Undergraduate Students at Princess of Naradhiwas University - บ่าวแช่มช้อย เกษรา; กำแหงกิจ รจเรข (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
This research aimed to 1) study students’ learning outcome; through blended learning 2) to compare effectiveness of students’ achievement through blended learning and 3) to evaluate blended learning in Information Searching and Academic Writing of Undergraduate Students at Princess of Naradhiwas University. The sample of this study was the first year accounting students group 1 Faculty of Management Science, Princess of Naradhiwas University who were registered in Information Searching and Academic Writing course in the second semester of the year 2017 there were 48 students. The research instruments were 1) blended learning’ teaching plan, 2) Evaluation form of students’ learning outcome, 3) information searching and academic writing comprehension test and 4) the blended learning questionnaire. The instruments were analyzed by reliability test. The reliability of evaluation form of students’ learning outcome was 0.782 that analyzed by Cronbach’s alpha coefficient and the reliability of the blended learning questionnaire was 0.863 that analyzed by KR-20 . The data of this study was analyzed by using Mean, Standard deviation (S.D.), Percentage and Effectivenesss Index (E.I.). The study found that: 1) The study of students’ learning outcome; through blended learning found that after teaching blended learning activities, the students were better on groups working, analytical thinking, practicing, submitting assignments on time, and the students learning outcome were highest level of all measuring and evaluating. 2) The effectiveness of students’ achievement through blended learning were higher than before using blended learning activities with 52.98%. 3) The evaluation blended learning found that 3.1) teacher, most students assume that teacher taught them easily to understand the lessons 3.2) content, most students assume that comprehensive content was suitable and they can adapt content in their everyday life; 3.3) teaching method, most students assume that teacher has good teaching techniques.